Analisis Kebijakan Kepala Sekolah dalam Pelaksanaan Kurikulum 2013 untuk meningkatkan Mutu Pendidikan di SMAN 8 Rejang Lebong - Ana, Fera Yuli; Warlizasusi, Jumira (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2021)
This writing has the main objective of obtaining information about the principal's policies in improving the quality of education at SMAN 8 Rejang Lebong. The principal's policy in improving the quality of education cannot be separated from the policies taken, the principal has broad authority in improving the quality of education in improving the quality of education, a policy from the principal is needed, especially in the implementation of the 2013 curriculum, the curriculum is an important part of the implementation of education schools to improve the quality of education by prioritizing curriculum development, especially the 2013 curriculum by developing teacher creativity in learning, creating a conducive atmosphere in learning, and fostering a sense of teacher responsibility in teaching. The method used is through a qualitative approach, in the implementation of the 2013 curriculum, teachers are given training, and facilities and infrastructure are provided to support learning, so as to create quality education in the hope of making education better, superior in the process, the results of the activities produce participants. students in accordance with the hopes and dreams of society at large to produce quality education.